REVISION OF ALBIZIA Sect. PACHYSPERMA (Leguminosae-Mimosoideae) - F. R. FOSBERG (Research Center for Biology, 1965)
In the course of revising the genus Serianthes Benth. (Reinwardtia 5: 293-317. 1960) it was necessary to account for several names which had been proposed in Serianthes but which applied to species belonging to a group that seems better placed in the genus Albizia. ) After some further study, the present treatment of this group, here regarded as constituting Albizia section Pachysperma, was brought together. Owing to the scarcity of material of most of the species concerned, as well as to the difficulty in understanding inflorescence morphology in some of the species from herbarium specimens alone, this paper is of necessity to be regarded as only preliminary. It may, however, serve to direct attention to the fact that the species involved do form a coherent group, with a number of common characters as well as a most peculiar inflorescence that needs much further study. Two new species and two new varieties, as well as two transfers, are proposed.